Development of the KALEM Technique as a Self-Regulation Model for Emotional Regulation Among Adolescents in Non-Formal Education - Endra Setyawan; Hiryanto Hiryanto (FKIP - Universitas Riau, 2026)
This study explores the implementation of the KALEM technique (Recognize, Acknowledge, Release Emotion, and Reframe Positively) as a self-help emotion regulation model for adolescents in non-formal education. Marginalized adolescents in equivalency programs often face academic trauma, social stigma, and severe emotional dysregulation, yet these institutions typically lack psychological support services. Using a descriptive exploratory qualitative approach, this study investigates how nine adolescents in the Package C program at PKBM Dharma Wangsa, Denpasar, utilize and experience this technique. Data were gathered through semi-structured interviews, participant observation, and reflective notes, then analyzed via thematic analysis and source triangulation. The findings reveal that the KALEM technique serves as an accessible, structured framework that enhances emotional awareness, reduces academic anxiety, and fosters active classroom participation. Rather than constructing a new structural model, this study elucidates how a simplified psychological tool can be successfully integrated into resource-limited non-formal environments. The four-step structure enables independent emotional management, offering a low-cost preventive approach to support the psychosocial well-being of non-formal learners.